IMPORTANCE OF PROBLEM SOLVING IN PHYSICS LESSONS - D. R.Masodiqova (Galaxy International Interdisciplinary Research Journal, 2023)
Issues solution-scientific knowledge and concepts system take over of means one counting. Knowledge and practical in character study and qualifications in possession issues solve of the process role very is big.